Stature from Tibia Irrespective of Sex: A Cross-Sectional Study - Devi, HR; Phanjoubam, M; Wahengbam, U; Frieny, L (Journal of Indian Academy of Forensic Medicine, 2024)
Mutilated human remains are recovered many times and may be the only evidence of crime. Establishing the identity of the victim is of  primary importance and stature assumes a prominent feature in the identification parameters. In view of this, we have taken up the present  study to on Indigenous Manipuri Meitei subjects, both males and females, in the age group of 21-25 years. This is a cross-sectional study  comparing the standing height of the participants with the percutaneous tibial length. The degree of correlation has been analysed and a  regression formula has been estableshed irrespective of sex, i.e., which can be used on any specimen, whether male or female. Atotal of 75  males and 75 females were studied in Department of Forensic Medicine and Toxicology, of a tertiary health care centre in north east India.  Subjects with any obvious congenital or acquired deformity of spine or extremities was not included in the study. Aregression equation is  established based on the tibial length of the individual, irrespective of sex has been derived as, Y= 81.90 +.85 X3 + 4.11. The equation so  developed is tested by F-test and found to be very highly significant (P=
Keywords: Stature; Tibia; Correlation; Meitei; Regression equation; Irrespective of sex